Functional Characterization of Novel Chitinase Genes Present in the Sheath Blight Resistance QTL: qSBR11-1 in Rice Line Tetep - Richa, Kamboj; Tiwari, Ila M.; Kumari, Mandeep; Devanna, B. N.; Sonah, Humira; Kumari, Archana; Nagar, Ramawatar; Sharma, Vinay; Botella, Jose R.; Sharma, Tilak R. (Frontiers in Plant Science, 2016)
Rice sheath blight disease caused by Rhizoctonia solani is one of the most devastating diseases in rice leading to heavy yield losses. Due to the polygenic nature of resistance, no major resistance gene with complete host resistance against R. solani has been reported. In this study, we have performed molecular and functional analysis of the genes associated with the major R. solani-resistance QTL qSBR11-1 in the indica rice line Tetep. Sequence analysis revealed the presence of a set of 11 tandem repeats containing genes with a high degree of homology to class III chitinase defense response genes. Real-time quantitative PCR analysis showed that all the genes are strongly induced 36 hours after R. solani infection. Comparison between the resistant Tetep and the susceptible HP2216 lines shows that the induction of the chitinase genes is much higher in the Tetep line. Recombinant protein produced in vitro for six of the eleven genes showed chitinolytic activity in gel assays but we did not detect any xylanase inhibitory activity. All the six in vitro expressed proteins show antifungal activity with a clear inhibitory effect on the growth of the R. solani mycelium. The characterized chitinase genes can provide an important resource for the genetic improvement of R. solani susceptible rice lines for sheath blight resistance breeding.